PENINGKATAN PEMBELAJARAN LEMPAR TURBO MELALUI PERMAINAN BOLA SASARAN (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research is to improve the learning outcomes of throwing a turbo on fifth grade students ofSDN 05 Tambakaji Semarang with the implementation of the target ball game. This study uses ClassroomAction Research (CAR). The subjects were fifth grade students of SDN 05 Tambakaji Semarang totaled 23students with research object throwing turbo boost learning outcomes. Data collection techniques usingdocumentation and observation through aspekkognitif assessment of learning outcomes, and aspects of theaffective aspects of psychomotor performance throwing the turbo. Data analysis techniques used in this researchis quantitative data (values student learning outcomes) that can be analyzed by descriptive and qualitativedata. The results showed that through ball toss game targets to improve learning outcomes throwing a turbo inthe first cycle to the second cycle. Learning outcomes throwing the ball in the goal in the first cycle completecategory is 47.82% or 11 students and students who have completed 12 or 52.17%. In the second cycle therewas an increase in the percentage of student learning outcomes in the category completed by 86.95% or 20students and children who have not completed 3 or 13.04%. Conclusion of this research is the application of aball toss game targets to improve learning outcomes throwing a turbo on fifth grade students of SDN 05Tambakaji Semarang.